2022
DOI: 10.3389/fneur.2022.830976
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation Could Modulate Cortical Excitability and the Central Cholinergic System in Akinetic Rigid-Type Parkinson's Disease: Pilot Study

Abstract: BackgroundTranscranial direct current stimulation (tDCS) is a non-invasive technique that has been widely studied as an alternative treatment for Parkinson's disease (PD). However, its clinical benefit remains unclear. In this study, we aimed to investigate the effect of tDCS on the central cholinergic system and cortical excitability in mainly akinetic rigid-type patients with PD.MethodsIn total, 18 patients with PD were prospectively enrolled and underwent 5 sessions of anodal tDCS on the M1 area, which is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…The study conducted by Oh et al [41] found a significant improvement in the BDI scores after anodal stimulation compared to the pre-tDCS measurements. The mean change in BDI scores was 2.67 ± 3.48, and this improvement was statistically significant with a p-value of less than 0.01.…”
Section: Effects Of Tdcs On Depression In Pdmentioning
confidence: 90%
See 1 more Smart Citation
“…The study conducted by Oh et al [41] found a significant improvement in the BDI scores after anodal stimulation compared to the pre-tDCS measurements. The mean change in BDI scores was 2.67 ± 3.48, and this improvement was statistically significant with a p-value of less than 0.01.…”
Section: Effects Of Tdcs On Depression In Pdmentioning
confidence: 90%
“…Oh et al [41] conducted a study with the objective of investigating how tDCS affects the central cholinergic system and cortical excitability in individuals primarily diagnosed with the akinetic-rigid type of PD. A total of 18 patients with PD participated in the study.…”
Section: Ma 25mentioning
confidence: 99%